2005
DOI: 10.1152/physiolgenomics.00229.2004
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the ascidian genome reveals novel insights into the molecular evolution of ion channel genes

Abstract: Ion fluxes through membrane ion channels play crucial roles both in neuronal signaling and the homeostatic control of body electrolytes. Despite our knowledge about the respective ion channels, just how diversification of ion channel genes underlies adaptation of animals to the physical environment remains unknown. Here we systematically survey up to 160 putative ion channel genes in the genome of Ciona intestinalis and compare them with corresponding gene sets from the genomes of the nematode Chaenorhabditis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
91
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 63 publications
8
91
1
Order By: Relevance
“…To determine the molecular basis for neuromuscular transmission, we characterized the nAChR subunits expressed in the larval muscle. In an earlier (13) and subsequent surveys of the Ciona genome, we identified 10 nAChR subunit genes and a rapsyn homolog gene ( Fig. 2A, Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…To determine the molecular basis for neuromuscular transmission, we characterized the nAChR subunits expressed in the larval muscle. In an earlier (13) and subsequent surveys of the Ciona genome, we identified 10 nAChR subunit genes and a rapsyn homolog gene ( Fig. 2A, Fig.…”
Section: Resultsmentioning
confidence: 98%
“…These cholinergic neurons project axons down the tail and innervate a part of the (mainly dorsal) muscle cells, whereas others receive excitation via gap junctions (8-11). Despite such knowledge, how the Ciona larva swims like fish using such simplified motor units remains unknown.Recent research on the Ciona genome provides an opportunity to examine the molecular mechanisms underlying the physiology of this animal (12,13). Given the correspondence between the body plans yet nevertheless the extreme contrast between their body complexities (minimal ascidian larva vs. much larger vertebrates), detailed comparison of their apparently similar swimming dynamics could uncover some novel control mechanisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence have suggested that whole genome duplications occurred before the vertebrate/ascidian divergence [39] and, later on, in the lineage of teleostheus after tetrapod divergence where only one set of these duplicated genes were maintained [40]- [43]. This is supported by the existence of several duplicated segments in zebrafish chromosomes [44].…”
Section: Genomic Organization Of P2x Orthologous Genesmentioning
confidence: 99%
“…Here, we instead used the ascidian chordate Ciona intestinalis, the closest living relative to vertebrates (16), which is thought to have just a single gluA gene (17). Ciona larvae are transparent, enabling easy identification of cells expressing a target gene and detection of morphological phenotypes in the tissues and organs.…”
mentioning
confidence: 99%